2022
DOI: 10.3389/fnhum.2022.895034
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Attention Network Correlates With High Traits of Emotion Dysregulation in Community Women — A Resting-State EEG Study

Abstract: In recent years, many studies have focused on resting-state brain activity, and especially on functional connectivity (FC), an approach that typically describes the statistical interdependence of activity in distant brain regions through specific networks. Our aim was to study the neurophysiological correlates of emotion dysregulation. Therefore, we expected that both the Default Mode Network (DMN), and the Ventral Attention Network (VAN) would have been involved. Indeed, the latter plays a role in the automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In another study, patients with MDD presented an abnormal increase in the rsFC between the medial thalamus and temporal areas, and a positive correlation was found between the thalamus‐temporal connectivity and the severity of depressive symptom (Brown et al, 2017 ). VAN is also called salience network occasionally (Seeley et al, 2007 ), and its core brain regions include the anterior insular and anterior cingulate cortex, which are mainly responsible for monitoring salient events and processing emotion, respectively (Fusina et al, 2022 ; Menon, 2011 ; Menon & Uddin, 2010 ; Riedel et al, 2018 ). Extensive studies have demonstrated the abnormal function of VAN in MDD (J. P. Hamilton et al, 2012 ; Y. Wang, Tang, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, patients with MDD presented an abnormal increase in the rsFC between the medial thalamus and temporal areas, and a positive correlation was found between the thalamus‐temporal connectivity and the severity of depressive symptom (Brown et al, 2017 ). VAN is also called salience network occasionally (Seeley et al, 2007 ), and its core brain regions include the anterior insular and anterior cingulate cortex, which are mainly responsible for monitoring salient events and processing emotion, respectively (Fusina et al, 2022 ; Menon, 2011 ; Menon & Uddin, 2010 ; Riedel et al, 2018 ). Extensive studies have demonstrated the abnormal function of VAN in MDD (J. P. Hamilton et al, 2012 ; Y. Wang, Tang, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous developments of psychiatric neuroscience, a range of neuroimaging techniques have been applied to the study of psychiatric diseases including electroencephalogram (EEG) ( 10 , 11 ), magnetoencephalography (MEG) ( 12 ), near-infrared spectroscopy (NIRS) ( 13 ), and functional magnetic resonance imaging (fMRI) ( 14 ). Among these techniques, EEG has excellent timing resolution and high time sensitivity, while being non-invasive and simple to operate ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a great variety of neuroimaging technologies have been used to reveal the neural activity of mental disorders, including functional Magnetic Resonance Imaging (fMRI) ( Wang et al, 2016 ), electromagnetic tomography (ETA) ( Clancy et al, 2020 ), and electroencephalogram (EEG) ( Newson and Thiagarajan, 2019 ; Fusina et al, 2022 ). Among these neurotechnical means, EEG is a non-invasive method to obtain electrophysiological signals, and has a high temporal resolution, which can directly measure the neural activity of the participant’s brain, describe the functional changes during its dynamic activities, and reflect the mental state of the participant.…”
Section: Introductionmentioning
confidence: 99%